In memoriam Jonathan C. Wright (1961–2019) - Katalin Szlavecz; Thomas Carefoot (ZooKeys, 2022)
The 11th International Symposium on Terrestrial Isopod Biology and this special issue of ZooKeys is dedicated to the memory of our colleague, Dr. Jonathan C. Wright, who passed away on December 16, 2019. Jonathan was a scientist, educator, musician, public servant, husband and father.